2008
DOI: 10.1099/mic.0.2008/017640-0
|View full text |Cite
|
Sign up to set email alerts
|

Unmarked insertional mutagenesis in the bovine pathogen Mycoplasma mycoides subsp. mycoides SC: characterization of a lppQ mutant

Abstract: Mycoplasma mycoides subspecies mycoides small colony (SC) is the aetiologic agent of contagious bovine pleuropneumonia (CBPP), a respiratory disease causing important losses in cattle production. The publication of the genome sequence of M. mycoides subsp. mycoides SC should facilitate the identification of putative virulence factors. However, real progress in the study of molecular mechanisms of pathogenicity also requires efficient molecular tools for gene inactivation. In the present study, we have develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…2 ). Lipoproteins of Mmm have previously been characterized as strong major antigens, e.g., LppB ( Ben1_0562 ) 14 , LppQ ( Ben1_1077 ) 15 16 , and variable surface protein Vmm ( Ben1_0422 ) 17 . In addition to these, we identified LppA ( Ben1_0014 ), LppC ( Ben1_1059 ), LppD ( Ben1_0685 ), and seven variable surface protein (VSP) genes in the genome ( Supplementary Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…2 ). Lipoproteins of Mmm have previously been characterized as strong major antigens, e.g., LppB ( Ben1_0562 ) 14 , LppQ ( Ben1_1077 ) 15 16 , and variable surface protein Vmm ( Ben1_0422 ) 17 . In addition to these, we identified LppA ( Ben1_0014 ), LppC ( Ben1_1059 ), LppD ( Ben1_0685 ), and seven variable surface protein (VSP) genes in the genome ( Supplementary Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a study to establish a DIVA diagnostic test to be used in combination with the CBPP live-attenuated vaccine, a very immunogenic antigen, LppQ was characterized and an LppQ-knock-out derivative of the T1/44 live attenuated vaccine strain, the T1LppQ-MT1 was created [ 18 20 ]. It was suggested that LppQ could be used in a DIVA assay for discriminating animals vaccinated with the depleted T1LppQ-MT1 strain from those infected with the strains from the field [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These could be identified by using larger groups of cattle or by measuring other immune response components such as IgM, IgA, or cellular responses. LppQ is known to be a marker of CBPP (1), but its usefulness as a vaccine is questionable based on recent studies (19,27). The results of this study indicate that MSC_1046 (LppQ) is the most significant component of the T1/44-induced response ( Fig.…”
Section: Discussionmentioning
confidence: 99%